Performance of testers with contrasting provitamin A content to evaluate provitamin A maize for resistance to Aspergillus flavus infection and aflatoxin production - Mboup, M.; Aduramigba-Modupe, A.O.; Sayadi Maazou, A.R.; Olasanmi, B.; Mengesha Abera, W.; Meseka, S.K.; Dieng, I.; Bandyopadhyay, R.; Menkir, A.; Ortega-Beltran, A. (Frontiers Media, 2023)
In sub-Saharan Africa (SSA), millions of people depend on maize as a primary staple. However, maize consumers in SSA may be exposed to malnutrition due to vitamin A deficiency (VAD) and unsafe aflatoxin levels, which can lead to serious economic and public health problems. Provitamin A (PVA) biofortified maize has been developed to alleviate VAD and may have additional benefits such as reduced aflatoxin contamination. In this study, maize inbred testers with contrasting PVA content in grain were used to identify inbred lines with desirable combining ability for breeding to enhance their level of resistance to aflatoxin. Kernels of 120 PVA hybrids generated by crossing 60 PVA inbreds with varying levels of PVA (5.4 to 51.7 µg/g) and two testers (low and high PVA, 14.4 and 25.0 µg/g, respectively) were inoculated with a highly toxigenic strain of Aspergillus flavus. Aflatoxin had a negative genetic correlation with β-carotene (r = −0.29, p < 0.0001) and PVA (r = −0.23, p < 0.0001), indicating that hybrids with high PVA content accumulated less aflatoxin than those with low to medium PVA. Both general combining ability (GCA) and specific combining ability (SCA) effects of lines and testers were significant for aflatoxin accumulation, number of spores, PVA, and other carotenoids, with additive gene actions playing a prominent role in regulating the mode of inheritance (GCA/SCA ratio >0.5). Eight inbreds had combined significant negative GCA effects for aflatoxin accumulation and spore count with significant positive GCA effects for PVA. Five testcrosses had combined significant negative SCA effects for aflatoxin with significant positive SCA effects for PVA. The high PVA tester had significant negative GCA effects for aflatoxin, lutein, β-carotene, and PVA. The study identified lines that can be used as parents to develop superior hybrids with high PVA and reduced aflatoxin accumulation. Overall, the results point out the importance of testers in maize breeding programs to develop materials that can contribute to controlling aflatoxin contamination and reducing VAD.